Chitin-induced systemic disease resistance in rice requires both OsCERK1 and OsCEBiP and is mediated via perturbation of cell-wall biogenesis in leaves - Takagi, Momoko; Hotamori, Kei; Naito, Keigo; Matsukawa, Sumire; Egusa, Mayumi; Nishizawa, Yoko; Kanno, Yuri; Seo, Mitsunori; Ifuku, Shinsuke; Mine, Akira; Kaminaka, Hironori (Frontiers in Plant Science, 2022)
Chitin is a well-known elicitor of disease resistance and its recognition by plants is crucial to perceive fungal infections. Chitin can induce both a local immune response and a systemic disease resistance when provided as a supplement in soils. Unlike local immune responses, it is poorly explored how chitin-induced systemic disease resistance is developed. In this study, we report the systemic induction of disease resistance against the fungal pathogen Bipolaris oryzae by chitin supplementation of soils in rice. The transcriptome analysis uncovered genes related to cell-wall biogenesis, cytokinin signaling, regulation of phosphorylation, and defence priming in the development of chitin-induced systemic response. Alterations of cell-wall composition were observed in leaves of rice plants grown in chitin-supplemented soils, and the disease resistance against B. oryzae was increased in rice leaves treated with a cellulose biosynthesis inhibitor. The disruption of genes for lysin motif (LysM)-containing chitin receptors, OsCERK1 (Chitin elicitor receptor kinase 1) and OsCEBiP (Chitin elicitor-binding protein), compromised chitin-induced systemic disease resistance against B. oryzae and differential expression of chitin-induced genes found in wild-type rice plants. These findings suggest that chitin-induced systemic disease resistance in rice is caused by a perturbation of cell-wall biogenesis in leaves through long-distance signalling after local recognition of chitins by OsCERK1 and OsCEBiP.